Engine quality early warning service method and system, readable medium and electronic equipment - YANG BENXIAO; ZHU DAN; LIU SHANGWEN; XIE KUAN; YUAN ZHILIN; ZHANG LIJIA; ZHAO SHENGXUAN; LIU XIAQING (2021)
The invention relates to an engine quality early warning service method and system, a readable medium and electronic equipment. The method comprises the steps of constructing an association analysis data table according to sensor detection data obtained from historical fault data and corresponding fault types; modeling the association rule of the engine fault to obtain a frequent item set on the association analysis data table; constructing an FP tree according to the correlation analysis data table and the minimum support degree of the engine fault; mining a frequent item set for the FP treeby using an FP-Growth algorithm; and sorting the mined frequent item sets in the set according to indexes to obtain a potential fault set. According to the method, potential faults which are not foundtemporarily but possibly exist can be found on the basis of the found engine faults, the potential faults of the engine can be mined in real time according to the detection data of the sensor, the service life of the engine i